Importance of biological markers in the assessment of endothelial dysfunction - Yu. S. Timofeev; M. A. Mikhailova; O. N. Dzhioeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
Endothelial dysfunction (ED) is a pathogenetic link in many cardiovascular diseases. One of the promising approaches to non-invasive diagnostics and assessment of the ED severity may be the determination of specific blood biomarkers. This review is devoted to the pathogenetic role of some biochemical and molecular factors associated with ED, as potential biomarkers of noncommunicable diseases.